2009
DOI: 10.1586/erv.09.55
|View full text |Cite
|
Sign up to set email alerts
|

The new ACAM2000™ vaccine and other therapies to control orthopoxvirus outbreaks and bioterror attacks

Abstract: Quarantine, case tracing and population vaccination facilitated the global eradication, in 1980, of variola virus, the causative agent of smallpox. The vaccines used during the eradication period, including Dryvax, the smallpox vaccine used in the USA, were live vaccinia and cowpoxvirus-based vaccines, which induced long-lasting and cross-protective immunity against variola and other related poxviruses. These vaccine viruses were produced by serial propagation in domesticated animals. The drawbacks to such ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…Our results showed that two-dose IMVAMUNE (6.26 ϫ 10 2 ) induced a higher peak level of NAbs (with day 0 at 30 days after the second vaccination) than Dryvax (2.38 ϫ 10 2 ) or Acambis2000 (8.94 ϫ 10 1 ). This is consistent with previous reports that "first-generation" vaccines induce similar higher levels of anti-VACV NAbs than "second-generation" vaccines (22), and it recapitulates findings (17) where, in human volunteers, two doses of MVA generated higher levels of NAbs than Dryvax alone. Similarly, in MPXV-infected NHP (13) and RPXV-infected rabbit challenge models (18), a twodose MVA regimen elicited higher levels of NAbs than Dryvax.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that two-dose IMVAMUNE (6.26 ϫ 10 2 ) induced a higher peak level of NAbs (with day 0 at 30 days after the second vaccination) than Dryvax (2.38 ϫ 10 2 ) or Acambis2000 (8.94 ϫ 10 1 ). This is consistent with previous reports that "first-generation" vaccines induce similar higher levels of anti-VACV NAbs than "second-generation" vaccines (22), and it recapitulates findings (17) where, in human volunteers, two doses of MVA generated higher levels of NAbs than Dryvax alone. Similarly, in MPXV-infected NHP (13) and RPXV-infected rabbit challenge models (18), a twodose MVA regimen elicited higher levels of NAbs than Dryvax.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our previous studies, 10 6 T cells adoptively transferred into nude mice failed to protect them from infection or to reduce viral loads (29). In contrast, BCV treatment in combination with an adoptive transfer of 10 5 or 10 4 T cells conferred survival to 100% or 60% of mice, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Of note, the specific cellular immune response triggered by nonreplicating poxvirus vectors is of the Th1 type, which may explain the weak antibody response elicited by these vectors (23,25). to be produced using highly attenuated smallpox vaccine strains such as, for instance, ACAM2000 (24).…”
Section: Discussionmentioning
confidence: 99%